Second round dataset: Impacts of Improved Bean Technology on Smallholder Productivity and Food Security in Burundi - Katungi, Enid Mbabazi; Nduwarugira, Eric; Ntukamazina, Jean Nepomuscene; Niragira Sanctus; Mutua, Mercy Muli; Kalemera, Sylvia Monica; Nchanji, Eileen Bogweh; Birachi, Eliud Abucheli; Rubyogo, Jean Claude (2025)
This data set complements the impact assessment data collected in round 1 from the same households. The data aimed to assess food and nutrition security through detailed dietary recalls for women of reproductive age (24-hour) and the entire household (7-day). Two rounds were necessary to avoid respondent fatigue Methodology:Researchers at ISABU collected the data after receiving training in the questions and use of tablets in both English and French languages. Prior to the actual survey, the questionnaires were translated from English into French, uploaded onto tablets and pretested on few selected farmers.